MTOR-driven quasi-programmed aging as a disposable soma theory: Blind watchmaker vs. intelligent designer - Blagosklonny, Mikhail V. (Landes Bioscience, 2013)
If life were created by intelligent design, we would indeed age from accumulation of molecular damage. Repair is costly and limited by energetic resources, and we would allocate resources rationally. But, albeit elegant, this design is fictional. Instead, nature blindly selects for short-term benefits of robust developmental growth. “Quasi-programmed” by the blind watchmaker, aging is a wasteful and aimless continuation of developmental growth, driven by nutrient-sensing, growth-promoting signaling pathways such as MTOR (mechanistic target of rapamycin). A continuous post-developmental activity of such gerogenic pathways leads to hyperfunctions (aging), loss of homeostasis, age-related diseases, non-random organ damage and death. This model is consistent with a view that (1) soma is disposable, (2) aging and menopause are not programmed and (3) accumulation of random molecular damage is not a cause of aging as we know it.